"Aspergillus niger" van Tieghem as toxic and allergenic mould in dwelling buildings after floods = "Aspergillus niger" van Tieghem jako toksyczny i alergogenny grzyb pleśniowy w obiektach budowlanych po powodziach - Piontek, Marlena; Bednar, Katarzyna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In last years problems of moulds in dwelling buildings becomes very important and vide broached in Europe and Poland territory. It?s not only for moulds in dampness buildings, but also as effect such disasters like floods. 76 species of moulds were detected on walls in dwellings therein from buildings after floods in the Lubuskie Province of which ten are the most common ones. Among those ten moulds, there are six species that, in the order of the most common allergens, cause an inflammatory condi-tion, namely: Penicillium chrysogenum, Aspergillus niger, Cladosporium herbarum, Aspergillus versicolor, Alternaria alternata, Aspergillus flavus.
Keywords: 4 Międzynarodowa konferencja "Ochrona i rekultywacja terenów dorzecza Odry: rekultywacja terenów zdegradowanych" (28-29.06.2007); moulds; housing buildings; flood bank; grzyby pleśniowe; budownictwo mieszkaniowe; powódź